Evaluation the frequencies of HLA alleles in moderate and severe COVID-19 patients in Iran: A molecular HLA typing study - Farhad Abolnezhadian; Sara Iranparast; Mojtaba Shohan; Zahra Shokati Eshkiki; Mahtab Hamed; Maryam Seyedtabib; Roohangiz Nashibi; Mohammad-Ali Assarehzadegan; Seyed Ali Mard; Ali Akbar Shayesteh; Niloofar Neisi; Manoochehr Makvandi; et al. (Heliyon, 2024)
Background: Severe acute respiratory syndrome coronavirus 2 was first reported in December 2019 and it has spread globally ever since. The HLA system is crucial in directing anti-viral immunity and recent studies are investigating the possible involvement of the HLA genes on the severity of immune inflammation in different phases of COVID-19. Methods: In this cross-sectional study, peripheral blood-extracted genomic DNAs of 109 COVID-19 patients and 70 healthy controls were genotyped for different alleles of HLA-A, HLA-B, and HLA-DRB1 loci using sequence-specific primer PCR method. Results: The results indicated that frequencies of HLA-DRB1*11:01 and HLA-DRB1*04:03 were significantly higher in severe patients rather than moderates (p: <0.001 and 0.004, respectively). Also, it was observed that HLA-DRB1*04:01 was more frequent in moderate patients and healthy controls (p:0.002). In addition, HLA-B*07:35, and HLA-DRB1*07:01 showed higher frequencies in patients compared with controls (p: 0.031 and 0.003 respectively). Inversely, due to the higher frequencies of HLA-B*51:01 (p:0.027), HLA-DRB1*11:05 (p:0.003), HLA-DRB1*13:05 (p:0.022), and HLA-DRB1*14:01 (p:0.006) in healthy individuals rather than patients, they may be associated with COVID-19 resistance. Conclusion: The results show that, based on the population differences, the type of alleles related to the severity of COVID-19 is different, which should be clarified by designing large-scale studies in order to develop HLA-based treatments and vaccines.